Rate of atrial fibrillation by Holter-Stroke Risk Analysis in undetermined TIA/rapidly improving stroke symptoms patients - Cannizzaro, F; Izquierdo, A; Cocho, D (Frontiers in Neurology, 2024)
Introduction: Holter SRA (Stroke Risk Analysis) is an automated analysis of ECG monitoring for Atrial Fibrillation (AF) detection. The aim of this study was to evaluate the rate of AF in undetermined TIA/ Rapidly improving stroke symptoms (RISS) patients. Methods: Prospective study of undetermined TIA / RISS patients who presented to the emergency department. Early vascular studies (angio CT, transthoracic echocardiography and ECG) were performed in emergency department. The Holter-SRA device was placed for 2 hours and the patients were classified into: confirmed AF, high risk of AF or low risk of AF. Prolonged ambulatory monitoring (7 days) was carried out every month for patients with a high-risk pattern. The results were evaluated until definitive detection of AF or low-risk pattern. The endpoints were rate of AF and vascular recurrence at 90 days. Results: Over a period of 24 months, 83 undetermined TIA/ RISS patients were enrolled. The mean age was 70±10 years and 61% were men. The median ABCD 2 score was 4 points (1-7). After 2 hours of monitoring in the emergency department, AF was detected in 1 patient (1.2%), 51 patients with a low-risk pattern and 31 patients (37.3%) showed a high-risk pattern of AF. During the ambulatory monitoring, of the 31 patients high risk pattern patients, AF was diagnosed to 17 cases and of the 51 patients with a low-risk pattern, one case experienced a recurrent vascular due to undetected AF (1.9% false negative). Three patients (3,6%) suffered a vascular recurrence within the first 90 days, before AF diagnosis. Conclusions: In our study, AF was detected in 22.9% of the 83 patients with indeterminate TIA/RISS. Holter-SRA has allowed us to increase the detection of AF, especially those patients with a high-risk pattern in the first 3 months.